Senam Kaki untuk Pencegahan dan Pengobatan Neuropati Perifer Diabetik pada Penderita Diabetes Mellitus - Tri Sumarni; Yuli Dwi Hartanto (LPPM Universitas Harapan Bangsa Purwokerto, 2023)
Diabetic peripheral neuropathy is the most common complication of DM. Diabetic neuropathy has a negative impact on peripheral foot and ankle function (strength and flexibility), thereby affecting daily physical activity and quality of life for people with DM. DM foot exercises are useful for strengthening intrinsic and extrinsic leg muscles and increasing flexibility, improving leg blood circulation so as to prevent complications of DM. This community service activity aims to increase the understanding of DM sufferers about DM foot care and improve skills related to DM foot exercises. The method of implementing the service is screening knowledge about foot care and DM foot exercise, counseling and discussion about DM foot care and DM foot exercise simulation. The target of the activity was DM sufferers, totaling 20. Most service participants were aged 61-70 years (55%), female (90%), had high blood sugar levels at the time (63%). Regarding knowledge about DM foot care, before counseling most were in the poor category (55%) and after counseling most were good (70%).